OPTIMALISASI BANK SYARI’AH MENUJU GOOD CORPORATE GOVERNANCE - Fahrur Ulum Fahrur Ulum (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2011)
Abstract: Syarî’ah banking must be optimized earnestly to fulfill the stakeholders interest. The effective implementation of cooporate governance would realize the goal of fairness, accountability, and transparancy. There are several prior focus of this system manager: basic concept and problems of cooperate governance in syarî’ah banking, the pillars of implementation, and the mechanism. As a result, to create an effective cooperate governance of syariah banking, the following aspects must be urgently required: a contract clarity, market discipline, moral dimension, socio-political atmosphere, law enforcement, and institution. Board of directors, senior management, stockholders, and depositors have important roles to establish the harmony of syariah banking development. The stakeholders are directly connected to the mechanism of cooperate governance of syariah banking. Key Words: corporate governance, bank syari’ah, stakeholders, dan mudlârabah